A Self‐Folding Polymer Film Based on Swelling Metal–Organic Frameworks. (23rd October 2018) - Troyano, Javier; Carné‐Sánchez, Arnau; Pérez‐Carvajal, Javier; León‐Reina, Laura; Imaz, Inhar; Cabeza, Aurelio; Maspoch, Daniel
Abstract: Herein, we exploit the well‐known swelling behaviour of metal–organic frameworks (MOFs) to create a self‐folding polymer film. Namely, we show that incorporating crystals of the flexible MOF MIL‐88A into a polyvinylidene difluoride (PVDF) matrix affords a polymer composite film that undergoes reversible shape transformations upon exposure to polar solvents and vapours. Since the self‐folding properties of this film correlate directly with the swelling properties of the MIL‐88A crystals, it selectively bends to certain solvents and its degree of folding can be controlled by controlling the relative humidity. Moreover, it shows a shape‐memory effect at relative humidity values from 60 % to 90 %. As proof of concept, we demonstrate that these composite films can lift cargo and can be used to assemble 3D structures from 2D patterns. Our strategy is a straightforward method for designing autonomous soft materials with folding properties that can be tuned by judicious choice of the constituent flexible MOF.